Penerapan Pendekatan Outcome-Based Education (OBE) dalam Penyusunan RPS Mata Kuliah Ilmu Pendidikan Islam di UIN Sumatera Utara - Febby Adinda; Burhandy; Fitri Diana; Siti Halimah (At-Tadris: Journal of Islamic Education, 2026)
The implementation of the Outcome-Based Education (OBE) approach has become an essential requirement in higher education to ensure the achievement of graduate competencies in accordance with national standards and the demands of the professional world, including in the course of Islamic Education Science. This study aims to analyze the application of the OBE approach in the preparation of the Semester Learning Plan (Rencana Pembelajaran Semester/RPS) for the Islamic Education Science course at UIN Sumatera Utara. This research employed a qualitative approach using document analysis methods on three RPS documents of the Islamic Education Science course used by the lecturers. The analysis focused on examining the alignment of RPS components with OBE principles, including the relationship between Program Learning Outcomes (PLO), Course Learning Outcomes (CLO), sub-CLOs, learning methods, and assessment systems. The results indicate that the RPS has been administratively well-prepared, with a 100% completeness of required components, and has integrated Islamic values as well as a variety of learning methods oriented toward student-centered learning. However, the implementation of OBE is still categorized as “adequate” because the formulation of CLOs and sub-CLOs has not yet been fully operational and measurable, the mapping of PLOs to CLOs has not been conducted systematically, and the linkage between assessment indicators and learning outcomes has not been explicitly articulated. These findings highlight the need to strengthen the substantive aspects of learning design so that the implementation of OBE in the Islamic Education Science course can be more optimal and truly oriented toward the achievement of student competencies.